"They sing our origins": a study of the lungsi drummers of Mampurugu - Davis, David C. (International Library of African Music, 1992)
The lungsi are a specialized segment of the Mamprusi population who serve as chroniclers of the past and recorders of the present. The unbroken historical narrative and royal genealogy which they retain and recite explain the origins of Mampurugu and serve as an ideological charter of the present political establishment on all levels. As such, these professionals are vital to the continuity of the traditional social and political system. The continuity of the traditions is directly linked to a reliable supply of these traditionists.
Keywords: African Music